Reference values for ductus venosus doppler indices of normal gestation at 22-37 weeks: A Vietnamese cohort study - Nguyen Thi Hong; Nguyen Minh Duc; Le Hoang; Phan Truong Duyet; Dang Hong Thien; Nguyen Thi Tuyet Mai; Hoang Thi Ngoc Tram; Ngo Minh Xuan; Huynh Quang Huy (MDPI AG, 2020)
Prenatal doppler ultrasound of the ductus venosus plays an important role in the evaluation of fetal circulation and fetal heart function. We aimed to establish the percentile of Resistivity Index (RI) and Pulsatility Index (PI) of the Ductus Venosus (DV) among normal Vietnamese fetuses with a gestation from 22 to 37 weeks in a cohort study. Normal Vietnamese fetuses with a gestation ranging from 22 to 37 weeks were examined in a cohort study. The PI and RI were recorded from the DV. We analyzed 640 participants who all fulfilled the inclusion and exclusion criteria of our study. Results: There was a significant correlation between RI, PI and gestational age as shown with the equations y = 0.077x - 0.003x2 + 3.493e - 5x3 (r=0.97) and y = 0.106x - 0.004x2 + 4.5e - 5x3 (r=0.94), respectively. A centile module was constructed for the DV RI and PI indices among normal Vietnamese fetuses with gestation from 22 to 37 weeks.